THE ROLE OF SOCIOLINGUISTIC COMPETENCE IN ENHANCING PROFESSIONAL AND ACADEMIC COMMUNICATION AMONG TECHNICAL UNIVERSITY STUDENTS - Temiov Jakhongir (Bright Mind Publishing, 2025)
Technical university students need to have good communication skills in addition to subject-specific knowledge in an increasingly interconnected world. Effective communication requires sociolinguistic competence, which is the capacity to use language in a variety of social and professional circumstances. The importance of sociolinguistic proficiency in academic and professional settings is examined in this essay, with a focus on technical students. It talks about the difficulties non-native English speakers encounter, how sociolinguistic competency affects professional achievement, and how to encourage self-directed learning to improve this ability.
Keywords: Communication, competence, sociolinguistic competence, background, learning, politeness, tone, register.